Partisipasi Kaum Muda dalam Pengembangan Komunitas Basis Gerejawi di Era Digital - Edita Tersa Risa; Yuliana Eni Yuliati (Jurnal Pelayanan Pastoral, 2023)
Social changes resulting from modernization and globalization can trigger society, especially young people, to become increasingly secular and individualistic. Growing secularism means that religious values ​​and spirituality are often seen as individual choices, not social obligations. individualism places great emphasis on personal freedom, autonomy, and self-achievement Loss of religious values ​​can lead to a lack of solid moral guidance in making decisions and acting. This of course brings very challenging changes and can sometimes make people easily become selfish and indifferent to church activities. The aim of this research is to determine the participation of young Catholics in developing the life of the KBG. In this research, the author used descriptive research. This is intended to discover, know and develop the truth in research. Based on the results of interviews with key informants, 90% of people are easily active in church activities both in the church and in the region/neighborhood. they are active not only as ordinary people but also as leaders or guides in various regional activities. This is caused first by the awareness of the youth themselves of the importance of participating in church activities. Second, there is support from KBG administrators, environmental administrators and local people for young people. People in region 6 really embrace young people and always give trust and support to easy people so that easy people feel comfortable in carrying out activities in the environment or region.